Inhibition of PDE1-B by Vinpocetine Regulates Microglial Exosomes and Polarization Through Enhancing Autophagic Flux for Neuroprotection Against Ischemic Stroke - Zang, Jiankun; Wu, Yousheng; Su, Xuanlin; Zhang, Tianyuan; Tang, Xionglin; Ma, Dan; Li, Yufeng; Liu, Yanfang; Weng, Ze’an; Liu, Xuanzhuo; Tsang, Chi Kwan; Xu, Anding; et al. (Frontiers in Cell and Developmental Biology, 2021)
Exosomes contribute to cell-cell communications. Emerging evidence has shown that microglial exosomes may play crucial role in regulation of neuronal functions under ischemic conditions. However, the underlying mechanisms of microglia-derived exosome biosynthesis are largely unknown. Herein, we reported that the microglial PDE1 expression was progressively elevated in the peri-infarct region after focal middle cerebral artery occlusion. By an oxygen-glucose-deprivation (OGD) ischemic model in cells, we found that inhibition of PDE1 by vinpocetine in the microglial cells promoted M2 and inhibited M1 phenotype. In addition, PDE1 inhibition significantly enhanced the autophagic flux in BV2 cells, and vinpocetine-mediated suppression of M1 phenotpye was dependent on autophagy in ischemic conditions. Co-culture of BV2 cells and neurons revealed that vinpocetine-treated BV2 cells alleviated OGD-induced neuronal damage, and treatment of BV2 cells with 3-MA abolished the observed effects of vinpocetine. We further demonstrated that ischemia and vinpocetine treatment significantly altered microglial exosome biogenesis and release, which could be taken up by recipient neurons and regulated neuronal damage. Finally, we showed that the isolated exosome per se is sufficient to regulate cortical neuronal survival in vivo. Taken together, these results revealed a novel microglia-neuron interaction mediated by microglia-derived exosomes under ischemic conditions. Our findings further suggest that PDE1 regulates autophagic flux and exosome biogenesis in microglia which plays a crucial role in neuronal survival under cerebral ischemic conditions.